RESPONSE OF DIFFERENT POTATO (SOLANUM TUBEROSUM L.) CULTIVARS TO VARIOUS CONCENTRATIONS OF BA (BENZYLADENINE) AND KINETIN UNDER IN VITRO CONDITIONS - HASSAN, ABDULQADIR M. AMIN; SARHAN, TAHA Z.; TOMA, RAFAIL S. (Journal of Duhok University, 2023)
This work was conducted at the plant tissue culture laboratory- Department of Horticulture, College of Agricultural Engineering Sciences, Duhok University, Kurdistan Region –Iraq. The study used tuber-eyes and node explants of four potatoes (Solanum tuberosum L.) cultivars "Sagitta, Challenger, SM 13-132-05, and Taurus" to assess the perform of these cultivars and the effects of various concentrations of BA (Benzyladenine) (0, 1, 2, 3, 4 mg.l-1) and kinetin (0, 1, 2, 3, 4 mg.l-1) in SM medium (7 mg.l-1 agar and 30 gm.l-1 sucrose) on in vitro shoot multiplication and roots regeneration. The results demonstrated that the Challenger cultivar in control treatment (zero concentration of BA and kinetin) was superior to the other cultivars under in vitro circumstances by producing the maximum shoot multiplication (4.90 shoots/ explant, 12.95 leaves/ explant, and 3.74 cm/ mean length of shoots). On the other hand, there were no appreciable variations in the four cultivars' responses to the various concentrations of BA and Kinetin in terms of the rooting percentage. The main note of this work is revels that MS medium with basic vitamins and solidified by agar can be used for potato plant production under in vitro conditions without the use of external plant growth regulators